2005
DOI: 10.1161/01.atv.0000152632.48937.2d
|View full text |Cite
|
Sign up to set email alerts
|

Pitavastatin Inhibits Remnant Lipoprotein-Induced Macrophage Foam Cell Formation Through ApoB48 Receptor–Dependent Mechanism

Abstract: Objective-Atherogenic remnant lipoproteins (RLPs) are known to induce foam cell formation in macrophages in vitro and in vivo. We examined the involvement of apoB48 receptor (apoB48R), a novel receptor for RLPs, in that process in vitro and its potential regulation by pitavastatin. Methods and Results-THP-1 macrophages were incubated in the presence of RLPs (20 mg cholesterol/dL, 24 hours) isolated from hypertriglyceridemic subjects. RLPs significantly increased intracellular cholesterol ester (CE) and triglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…In addition to many recent studies concerning the inhibitory effects of pitavastatin on aortic smooth muscle cells and vascular endothelial cells [17][18][19][20] , there are reports of the suppressive effects of pitavastatin on macrophage accumulation and functions. Pitavastatin enhanced the expression of SR-B in macrophages which can reduce the development of atherosclerotic lesions through the inactivation of the transcription factor NF-kappaB 13) and inhibition of the RLP-induced formation of foam cells by macrophages partly through the regulation of the apoB48 receptor 14) . A recent experimental study by Suzuki et al showed that 16 weeks of treatment with pitavastatin reduced the macrophage-positive area in the rabbit aortic plaque by 39.4% and increased the areas occupied by collagen and alpha-smooth muscle actin (alpha-SMA) by 66.4 and 91.7%, respectively 21) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to many recent studies concerning the inhibitory effects of pitavastatin on aortic smooth muscle cells and vascular endothelial cells [17][18][19][20] , there are reports of the suppressive effects of pitavastatin on macrophage accumulation and functions. Pitavastatin enhanced the expression of SR-B in macrophages which can reduce the development of atherosclerotic lesions through the inactivation of the transcription factor NF-kappaB 13) and inhibition of the RLP-induced formation of foam cells by macrophages partly through the regulation of the apoB48 receptor 14) . A recent experimental study by Suzuki et al showed that 16 weeks of treatment with pitavastatin reduced the macrophage-positive area in the rabbit aortic plaque by 39.4% and increased the areas occupied by collagen and alpha-smooth muscle actin (alpha-SMA) by 66.4 and 91.7%, respectively 21) .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, atherogenic remnant lipoproteins (RLPs) are known to induce foam cell formation from macrophages in vitro and in vivo. An in vitro study by Kawakami demonstrated that pitavastatin inhibited the RLP-induced formation of foam cells by macrophages, at least in part, through regulation of the involvement of the apoB48 receptor, a novel receptor for RLPs 14) . These preventative actions of pitavastatin suggested that the drug can also beneficially regulate resistin levels, which may lead to improvements in insulin resistance and atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…It recognizes apoB48 or its equivalent domain of apoB100 of TRLs, and takes up CM, CM remnant, HTG-VLDL, and VLDL remnant, but not nascent VLDL or LDL. We examined the involvement of apoB48 receptor in RLP-induced foam cell formation in macrophages (23). In our experiments, siRNA against apoB48 receptor significantly suppressed their expression in THP-1 macrophages, and inhibited RLP-induced foam cell formation.…”
Section: Rlp and Monocyte/macrophagesmentioning
confidence: 95%
“…Furthermore, as nicely reviewed by Fujioka et al 29) , increased remnant lipoproteins (mainly chylomicron remnants) contribute to form atherosclerotic lesions through a variety of mechanisms. It was demonstrated that chylomicron remnants invade directly into the subendothelial spaces of arteries and are taken up by macrophages via several receptors, such as LDL receptor-related protein (LRP) or apoB-48 receptor, resulting in macrophage foam cell formation [30][31][32][33] . We reported that increased serum chylomicron remnants are directly associated with enhanced carotid atherosclerosis in subjects with apparently normal TG levels 34) .…”
Section: ) Increased Lipoprotein Remnants and Postprandial Hyperlipimentioning
confidence: 99%